1995
DOI: 10.1093/oxfordjournals.humrep.a135934
|View full text |Cite
|
Sign up to set email alerts
|

Immunology: Chlamydial immunoglobulin IgG and IgA antibodies in serum and semen are not associated with the presence of Chlamydia trachomatis DNA or rRNA in semen from male partners of infertile couples

Abstract: The role of Chlamydia (C.) trachomatis in male infertility is controversial. The objective of this study was to determine the prevalence of asymptomatic C. trachomatis infections in male partners of infertile couples, and to compare this result with the presence of chlamydial antibodies in serum and semen. C.trachomatis was detected in five of 50 semen specimens (10%) by either polymerase chain reaction for C. trachomatis DNA or direct DNA probing for C. trachomatis rRNA. There was no association between the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
3
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 0 publications
6
39
3
4
Order By: Relevance
“…The presence of C. trachomatis in semen emphasizes the potential risk of this route of transmission, and underlines the need for sensitive direct detection methods in this group of patients (Dieterle et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of C. trachomatis in semen emphasizes the potential risk of this route of transmission, and underlines the need for sensitive direct detection methods in this group of patients (Dieterle et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to resolve this issue, since chlamydiae present in semen could be transmitted by adhering to spermatozoa, which may serve as vectors, spreading the pathogen to the uterus and Fallopian tubes. In fact, studies have reported finding spermatozoa with adhering chlamydial bodies in the peritoneal fluid of women with salpingitis at laparoscopy (Friberg et al, 1987).The presence of C. trachomatis in semen emphasizes the potential risk of this route of transmission, and underlines the need for sensitive direct detection methods in this group of patients (Dieterle et al, 1995).Screening with classical cell culture requires specimens from endo-urethral swabs, which are unacceptable to many asymptomatic men. The cell culture method cannot be used for semen and urine samples due to their cytotoxicity (Mardh et al, 1980), and is not sufficiently sensitive to rule out infections of accessory glands (Berger et al, 1978).…”
mentioning
confidence: 99%
“…The differences may be due in part to the type of study carried out in these populations, different diagnostic tests, or different preparation of samples [25]. The effect of C. trachomatis on male fertility is not yet established, since infected men do not show alterations in semen analysis [9,11,12]. On the other hand, C. trachomatis may adhere to and penetrate the sperm, causing infection and, later on, infertility by decreasing motility and/or sperm count [10].…”
Section: Discussionmentioning
confidence: 99%
“…The female reproductive tract can be colonized by this microorganism during sexual intercourse and assisted reproduction procedures and this infection may cause infertility [3,9,11,12,33]. Although the presence of IgA antibodies to C. trachomatis in semen is not associated with alterations in seminal parameters or inflammatory response in male reproductive tract, these antibodies could indicate a risk factor for STD for couples of asymptomatic infertile men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation